1998
DOI: 10.1099/0022-1317-79-8-2059
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and genome structure of grapevine rupestris stem pitting associated virus-1 reveal similarities to apple stem pitting virus.

Abstract: Rupestris stem pitting (RSP), a component of the rugose wood complex, is one of the most widespread graft-transmissible diseases of grapevines. Here we report on the consistent association of a high molecular mass dsRNA (ca. 8n7 kbp) with RSP. The dsRNA was reverse-transcribed and cDNAs generated were cloned into Lambda ZAP II. Sequence analysis of the cDNA clones showed that the dsRNA was of viral origin and the putative virus was designated rupestris stem pitting associated virus-1 (RSPaV-1). The genome of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
14

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 21 publications
1
58
0
14
Order By: Relevance
“…It was reported that the genomic diversity of GVA has been examined based on the analysis of partial or complete coat protein gene (CP), because it had a certain degree of variability (Goszczynski and Jooste, 2003;Murolo et al, 2008). It was reported that the genomic diversity of GRSPaV has been examined based on the analysis of partial or complete RNA-dependent RNA polymerase gene (RdRp) (ORF 1), which is one of the most conserved regions of the GRSPaV genome (Meng et al, 1998;Lunden et al, 2010). Characterizing virus isolates is an important aspect of the development of tools for the detection of this virus, the information about sequence diversity among variants may help to select regions of the virus genome targeted for specific virus detection and to design primers for reliable detection of all known virus variants.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the genomic diversity of GVA has been examined based on the analysis of partial or complete coat protein gene (CP), because it had a certain degree of variability (Goszczynski and Jooste, 2003;Murolo et al, 2008). It was reported that the genomic diversity of GRSPaV has been examined based on the analysis of partial or complete RNA-dependent RNA polymerase gene (RdRp) (ORF 1), which is one of the most conserved regions of the GRSPaV genome (Meng et al, 1998;Lunden et al, 2010). Characterizing virus isolates is an important aspect of the development of tools for the detection of this virus, the information about sequence diversity among variants may help to select regions of the virus genome targeted for specific virus detection and to design primers for reliable detection of all known virus variants.…”
Section: Discussionmentioning
confidence: 99%
“…O Rupestris stem pitting-associated virus (RSPaV), família Flexiviridae, gênero Foveavirus, agente causal das caneluras do tronco de Rupestris, possui partículas alongadas e flexuosas com cerca de 800 x 12 nm, CP de 28 kDa e genoma de RNA de fita simples e senso positivo com 8726 nucleotídeos (nt), organizado em cinco ORFs. A ORF5 (nt 7770 a 8549) A ORF5 (nt 7770 a 8549) codifica o gene CP (Meng et al, 1998;Zhang et al, 1998;Fauquet et al, 2005).…”
Section: Introductionunclassified
“…These included development of rapid serological detection of viruses infecting a range of plants, including woody plants (62), vegetables (51), and others such as cardamom (28); development of pseudorecombinants of multicomponent viruses (6, 32); and cross-protection studies on zucchini yellow mosaic (55), tomato ringspot (2), and tomato spotted wilt (57) viruses. Later work led to development and testing of virus-resistant transgenic vegetables (12-14, 22, 58); some work on the mechanism of transgenic virus resistance (40)(41)(42); sequencing of viral genomes (33,38,63); and risk assessment studies of virus-resistant transgenic plants (11). I also did a lot of international work on a range of viruses, which helped to attract numerous graduate students, postdoctoral associates, and scientists to my laboratory.…”
Section: Synopsis Of My Research Effortsmentioning
confidence: 99%